PENINGKATAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF (TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM, (STUDI KASUS: KELAS IV SDN 1 SUMBERKOLAK KABUPATEN SITUBONDO) - Reky Lidyawati (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2016)
The learning model is applied to the first public elementary school in sumberkolak still not up to greater student learning, student learning outcomes are still low, so it took a new breakthrough in learning. This research will focus on improving student learning outcomes through the implementation of cooperative learning model student team achievement division on the subjects of Islamic religious education. Using the model of classroom action research using these 2 cycles the researchers will try to improve student learning outcomes. From the research that has been conducted has shown that cooperative learning model STAD learn some vital lessons can improve student outcomes, this is evidenced by an increase learning outcomes from cycle 1 to cycle 2 by 30%